Identificación de insectos polinizadores, usando la aplicación iNaturalist en el cultivo de chocho (Lupinus mutabilis Sweet), basada en la utilización de pesticidas para la producción, en 5 parroquias de la provincia de Cotopaxi 2021. - Yupa Ortiz, Ana Gabriela (2022)
Pollinating insects are in danger of extinction due to the indiscriminate use of pesticides and the lack of knowledge on the part of farmers about the function of each insect. This research was conducted in five parishes belonging to the province of Cotopaxi (Aláquez, Cochabamba, Cusubamba, Guaytacama, and Pujilí), where chocho is produced, with conventional agriculture based on the use of synthetic fertilizers and pesticides for phytosanitary control, having as specific objectives the identification, abundance, dominance, and diversity of pollinating insects. With chromatic traps (yellow plates), soap, and water, when the crop presented 50% of flowering. In the results obtained in this research, 18 specimens were identified as pollinating insects of the chocho crop (Lupinus mutabilis Sweet) at the genus level, belonging to 13 families of four orders: Astylus, Eristalis, Platycheirus, Toxomerus, Chrysomya, Cynomya, Hedriodiscus, Tachina, Dilophus, Tipula, Nephrotoma, Megachile, Apis, Caenohalictus, Mythimna, and Lon. According to the multivariate analysis of the climatic conditions (temperature, precipitation) and altitude, the parishes with the lowest rainfall have the highest abundance of insects. The variable rain and size affect the presence of pollinating insects. With the diversity and dominance of insects, the Shannon-Wiener index in the five sectors understudy has a low variety. As for the supremacy of Simpson, the results were inversely proportional to each other.